An Overview of the Current State of Linked and Open Data in Cataloging - Ullah, Irfan; Khusro, Shah; Ullah, Asim; Naeem, Muhammad (Information Technology and Libraries, 2018)
Linked Open Data (LOD) is a core Semantic Web technology that makes knowledge and information spaces of different knowledge domains manageable, reusable, shareable, exchangeable, and interoperable. The LOD approach achieves this through the provision of services for describing, indexing, organizing, and retrievingknowledge artifacts and making them available for quick consumption and publication. Thisis also alignedwith the role and objective of traditional library cataloging. Owing to this link, majorlibraries of the world are transferring their bibliographic metadata to the LOD landscape. Some developments in this direction include the replacement of Anglo-American Cataloging Rules 2nd Edition by the Resource Description and Access (RDA) and the trend towards the wideradoption of BIBFRAME 2.0. An interestingand related development in this respect arethe discussions among knowledge resources managers and library community on the possibility of enriching bibliographic metadata with socially curated or user-generated content. The popularity of Linked Open Data and its benefit to librarians and knowledge management professionals warrant a comprehensive survey of the subject. Althoughseveral reviews and survey articles on the application of Linked Data principles to cataloging have appeared in literature, a generic yet holistic review of the current state of Linked and Open Data in cataloging is missing. To fill the gap, the authors have collected recent literature (2014–18) on the current state of Linked Open Data in cataloging to identify research trends, challenges, and opportunities in this area and, in addition, to understand the potential of socially curated metadata in cataloging mainlyin the realm of the Web of Data. To the best of the authors’ knowledge, this review article is the first of its kind that holistically treats the subject of cataloging in the Linked and Open Data environment. Some of the findings of the review are: Linked and Open Data is becoming the mainstream trend in library cataloging especially in the major libraries and research projects of the world; with the emergence of Linked Open Vocabularies (LOV), the bibliographic metadata is becoming more meaningful and reusable; and, finally, enriching bibliographic metadata with user-generated content is gaining momentum.Conclusions drawn from the study include the need for a focus on the quality of catalogued knowledge and the reduction of the barriers to the publication and consumption of such knowledge, and the attention on the part of library community to the learning from the successful adoption of LOD in other application domains and contributing collaboratively to the global scale activity of cataloging.